Cyber Fraud with Profile Cloning Mode in The Perspectives of Cyberculture and Space Transition Theory - Yulistiyo, Wily; Fadillah, Firman; Gibran, Andi (Sekolah Tinggi Ilmu Kepolisian, 2024)
This study aims to investigate whether there are still any society who do not understand cyber culture on social media which then has the potential to become victims of cyber fraud crimes. In the digitalization era 4.0, people tend to use technology to do various activities and meet their needs, including online transactions for goods and services using various digital platforms and social media. The high activity on the Internet is also accompanied by opportunities for crimes by utilizing the internet media. One of the cases that is increasingly occurring in the digitalization era is cyber fraud with profile cloning mode. The author is interested in studying cyber fraud in Wajo Police because the mode used was profile cloning, which used the profile of a law enforcer to make fictitious buying and selling. This study used a qualitative approach and a case study method to conduct an in-depth analysis of cyber fraud cases with profile cloning mode. The results of the study show that there are still people who do not understand cyberculture on social media, so they have the potential to be victims of cyber fraud crimes. Moreover, the results of the study also show that perpetrators commit cyber fraud with profile cloning mode due to the pressure in real life and the ease of cloning accounts on social media. Thus, such circumstances provoke perpetrators to shift their evil deeds to cyberspace.